Numerical study of flow in a 2D boiler - Bauer, Petr; Klement, Vladimír; Strachota, Pavel; Žabka, Vítězslav (Proceedings of the Conference Algoritmy, 2015)
We present a numerical study of  ow in a 2D chamber of a simplied industrial boiler. The study features multiple cases of  ow with dierent inlet settings. The mathematical model is based on the incompressible Navier-Stokes equations and solved numerically by means of finite element method. The time discretization is semi-implicit and the resulting linear systems are solved using multigrid solver parallelized via OpenMP. The goal of this study is to provide reference data for a complex model of coal combustion that is being veried.